2020
DOI: 10.1177/1357633x20969531
|View full text |Cite
|
Sign up to set email alerts
|

Barriers, access and management of paediatric epilepsy with telehealth

Abstract: Access to paediatric neurology care is complex, resulting in significant wait times and negative patient outcomes. The goal of the American Academy of Pediatrics National Coordinating Center for Epilepsy's project, Access Improvement and Management of Epilepsy with Telehealth (AIM-ET), was to identify access and management challenges in the deployment of telehealth technology. AIM-ET organised four paediatric neurology teams to partner with primary-care providers (PCP) and their multidisciplinary teams. Telehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…[8] Research by Gali et al reported 94% parental and 100% physician satisfaction from telemedicine interventions among total 61 respondents. [9] Study by Dayal et al discussed the differences between the over 13,000 in-person and over 1,000 telemedicine appointment groups. It has been noted, that telemedicine group came from nonprivate insurance, lower income and lower education.…”
Section: Description Of the State Of Knowledgementioning
confidence: 99%
“…[8] Research by Gali et al reported 94% parental and 100% physician satisfaction from telemedicine interventions among total 61 respondents. [9] Study by Dayal et al discussed the differences between the over 13,000 in-person and over 1,000 telemedicine appointment groups. It has been noted, that telemedicine group came from nonprivate insurance, lower income and lower education.…”
Section: Description Of the State Of Knowledgementioning
confidence: 99%
“…A multi-center study evaluating wait-times and improvement of access for pediatric patients with Epilepsy to specialists was conducted using a design similar to ours. A total of 73 visits completed by 61 patients/family members found telehealth visits to enhance access to physicians and reduce cost, missed school hours and missed work hours ( Gali et al, 2020 ). In a Spanish study, authors report their experience with telemedicine services for epilepsy care.…”
Section: Discussionmentioning
confidence: 99%
“…It is a digital solution in health care that can provide quality care, increase timely access, minimise travel distances and reduce costs. [2] The World Health Organization explains the concept of telemedicine as: "the provision of healthcare where distance is a decisive factor, all healthcare professionals using information and telecommunications technologies to exchange valid information for the diagnosis and prevention of disease and injury, research and evaluation, and other education of healthcare providers, all in order to improve the health of individuals and their communities. In view of definitions above, the World Health Organization further recognizes four characteristics of telemedicine: 1. the purpose of telemedicine is to provide clinical support; 2. the purpose of telemedicine is to overcome geographical barriers and connect users who are not in the same physical location; 3. telemedicine involves the use of different types of information and telecommunication technologies; and 4. the aim of telemedicine is to improve health care outcomes.…”
Section: Research Backgroundmentioning
confidence: 99%